Considerações acerca do imaginário, das representações sobre o mal é de şua evolução da antiguidade clássica romana à antiguidade tardia - Esteves, Germano Miguel Favaro [UNESP] (FapUNIFESP (SciELO), 2016)
Through an evolutionary analysis of representations of Evil, in Christian point of view, from Classical Roman Antiquity to Late Antiquity, this article aims to present, inserted in this scope, a dialogue between the main sources from the Early Church to the Patristic, presenting an overview of how the Christian writers thought and voiced, in the theological and hagiographic literature, the imaginary representations about the Evil. By indicating the propositions of Christian writers of the mentioned period it could be seen a slow and gradual change in thinking about the representations of Evil, in different situations present in the analysis process of such sources in the long term.
Considerations about imaginary, representations of the evil and its evolution from the Roman classical antiquity to late antiquity
Keywords: Christianity; Evil; Hagiographies; Late antiquity; Theology